Novel mutations in PLCZ1 lead to early embryonic arrest as a male factor - Lin, Yunying; Huang, Yi; Li, Boyu; Zhang, Ting; Niu, Yichao; Hu, Shuanggang; Ding, Ying; Yao, Guangxin; Wei, Zhe; Yao, Ning; Yao, Yejie; Lu, Yao; et al. (Frontiers in Cell and Developmental Biology, 2023)
Early embryonic arrest is one of the causes of assist reproduction technology (ART) failure. We have previously reported that the first sperm-derived genetic factor, ACTL7a mutations, could lead to early embryonic arrest. However, whether there are other male genetic factors associated with early embryonic arrest remains elusive. Here, we reported bi-allelic mutations in PLCZ1, the well-known causal gene of total fertilization failure, in four infertile males. Among these mutations, p.403_404del, p.I489S, and p.W536X were newly reported in this study. Histological and western-blotting analysis of the patients’ sperm indicated these variants as loss-of-function mutations. These patients manifested normal conventional semen parameters and ultra-structures in sperm heads. However, among four in vitro fertilization (IVF) cycles, 81.8% (18/22) of the oocytes were polyspermic fertilized, which was rarely reported in PLCZ1-related male patients. In the following six ICSI cycles, artificial oocyte activation (AOA) was applied and successfully rescued the fertilization failure and polyspermy phenotypes, with 31.3% (15/48) of the MII oocytes normally fertilized. However, 60.0% (9/15) of these normally fertilized zygotes were arrested at 2-5-cell stage, with one failing to cleave, indicating that PLCZ1 was not only necessary for fertilization, but also crucial for early embryonic development. However, these rescued zygotes showed a lower potential in developing into blastocysts when cultured in vitro. Thus, fresh cleavages transfer was tried and two live births were successfully achieved thereafter. In conclusion, this study provided novel mutations in PLCZ1 gene to expand the pathogenic mutational spectrum in male infertility and demonstrated that PLCZ1 was a crucial sperm-related genetic factor for early embryonic arrest. We also proposed that cleavage transfer after ICSI and AOA treatment could be a potential treatment method for male patients carrying bi-allelic mutations in PLCZ1.